Clinical outcomes according to symptom presentation in patients with acute myocardial infarction: Results from the FAST‐MI 2010 registry. Issue 12 (15th December 2017) - Puymirat, Etienne; Aissaoui, Nadia; Bonello, Laurent; Cayla, Guillaume; Labèque, Jean‐Noel; Nallet, Olivier; Motreff, Pascal; Varenne, Olivier; Schiele, François; Ferrières, Jean; Simon, Tabassome; Danchin, Nicolas; et al.
Abstract : Background: Atypical clinical presentation in acute myocardial infarction (AMI) patients is not uncommon; most studies suggest that it is associated with unfavorable prognosis. Hypothesis: Long‐term clinical impact differs according to predominant symptom presentation (typical chest pain, atypical chest pain, syncope, cardiac arrest, or dyspnea) in AMI patients. Methods: FAST‐MI 2010, a nationwide French registry, included 4169 patients with AMI in 213 centers at the end of 2010 (76% of active centers). Demographics, medical history, hospital management, and outcomes were compared according to predominant symptom presentation. Results: Typical chest pain with no other symptom was reported in 3020 patients (68% in STEMI patients, 76% in NSTEMI patients). Atypical chest pain, dyspnea, syncope, and cardiac arrest were reported in 11%, 11%, 5%, and 1%, respectively. Patients with atypical clinical presentation had a higher cardiovascular risk profile and received fewer medications and a less invasive strategy. Using Cox multivariate analysis, atypical chest pain was not associated with higher death rate at 3 years (HR: 0.96, 95% CI: 0.69‐1.33, P = 0.78), whereas cardiac arrest (HR: 2.44, 95% CI: 1.00‐5.97, P = 0.05), syncope (HR: 1.70, 95% CI: 1.18‐2.46, P = 0.005), and dyspnea (HR: 1.66, 95% CI: 1.31‐2.10, P < 0.001) were associated with higher long‐term mortality compared with patients with typical isolated chest pain. Similar trends were observed in STEMI and NSTEMI populations. Conclusions: Atypical clinical presentation is observed in about 20% of AMI patients. Cardiac arrest, dyspnea, and syncope represent independent predictors of long‐term mortality in STEMI and NSTEMI populations.